2021
DOI: 10.1186/s13059-021-02322-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of enhancer action: the known and the unknown

Abstract: Differential gene expression mechanisms ensure cellular differentiation and plasticity to shape ontogenetic and phylogenetic diversity of cell types. A key regulator of differential gene expression programs are the enhancers, the gene-distal cis-regulatory sequences that govern spatiotemporal and quantitative expression dynamics of target genes. Enhancers are widely believed to physically contact the target promoters to effect transcriptional activation. However, our understanding of the full complement of reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
173
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(185 citation statements)
references
References 294 publications
(191 reference statements)
10
173
0
2
Order By: Relevance
“…The presence of these proteins on nascent chromatin may directly block the spread of H3 K9 methylation or may function to promote the localized assembly of open chromatin (Figure 7A ). The latter possibility is consistent with the active enhancer-like structure of the HAT1-dependent sites of accessibility in constitutive heterochromatin, given the central role of bromodomain proteins in the formation of active enhancers in the context of euchromatin ( 91 ).…”
Section: Discussionsupporting
confidence: 75%
“…The presence of these proteins on nascent chromatin may directly block the spread of H3 K9 methylation or may function to promote the localized assembly of open chromatin (Figure 7A ). The latter possibility is consistent with the active enhancer-like structure of the HAT1-dependent sites of accessibility in constitutive heterochromatin, given the central role of bromodomain proteins in the formation of active enhancers in the context of euchromatin ( 91 ).…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, it has been shown that very distal enhancers can control gene expression, indicating that open regions of chromatin may not necessarily regulate the most proximal gene ( Lettice et al 2003 ; Amano et al 2009 ; Lacomme et al 2018 ). Most changes in accessibility occur in distal nonpromoter regions (Supplementary Figure S4C; Thurman et al 2012 ; Pliner et al 2018 ; Friman et al 2019 ), and deciphering the relationship between gene expression and cis -regulatory regions has been a topic of immense focus ( Ackermann et al 2016 ; Gonen et al 2018 ; Zhao et al 2019 ; Cai et al 2020 ; Cunningham et al 2021 ; Panigrahi and O’Malley 2021 ). Our study serves as a foundation to probe open chromatin regions and potential regulatory functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recruiting activators such as VP64, Mediator and SIX3 to this enhancer also increased the enhancer–promoter distance whilst upregulating Shh expression [ 407 ]. It has been argued that this might be due to increased enhancer mobility [ 408 ] whereby non-thermal energy produced during transcription can “stir” the chromatin [ 312 ]. However, whilst this stirring model predicts that the enhancer explores a larger nuclear space, it also moves faster, which would potentially increase the frequency of contacts with the gene promoter [ 312 ].…”
Section: Enhancer–promoter Communication In Three Dimensionsmentioning
confidence: 99%